PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN REMAJA PUTRA TENTANG BAHAYA ALKOHOL DI DESA MOLOSIPAT UTARA KECAMATAN POPAYATO BARAT KABUPATEN POHUWATO - Rona Febriyona; Inne Ariane Gobel (-, 2021)
Alcohol is a substance that is most often misused by humans. The purpose of this study was to determine the effect of health education on the knowledge of young men about the dangers of alcohol. Design that is quasy experimental pre-post test. The population in this study amounted to 60 adolescents and a sample of 30 respondents with sampling techniques namely simple random sampling, and showed a paired T-test. The results the knowledge of the experimental group, 0.000 (p <0.05) and the control group 0.231 (p <0.05). Which means there is an influence of health education on the knowledge of young men about the dangers of alcohol in the village of North Molosipat Popayato District West District of Pohuwato? It is expected that the community, the village government and health workers will cooperate with the police to control the behavior of adolescents in the case of drinking alcoholic beverages (alcoholic beverages, so as to avoid criminal acts and traffic accidents).